ANALISIS TERHADAP PEMBATASAN PERLINDUNGAN HAK KEBEBASAN BEREKSPRESI DALAM MEDIA SOSIAL MENURUT HUKUM HAM INTERNASIONAL - Aziza Zulia Zaini; Aji Wibowo (Fakultas Hukum Universitas Trisakti, 2021)
Court Decision Number 274.Pdt.Sus-PKPU/2020/PN Niaga.Jkt.Pst is a lawsuit filed by workers due to non-implementation of the Decision from Industrial Relations Court by PT. Sari Keramindo International. The main problems: how the authority of Central Jakarta Commercial Court in examining and deciding disputes between workers and PT. Sari Keramindo International and how is the dispute resolution process in homologation decisions between workers and PT. Sari Keramindo International based on the regulations. This research is normative descriptive legal research trough literature studies, analyzed qualitatively and conclusions are drawn using deductive methods. The conclusion: Commercial Court has authority to adjudicate disputes between workers and PT. Sari Keramindo International due to wages and severance pay which can categorized as debt arising from law due to the non-implementation of the decision of Industrial Relations Court and provisions in Article 1149 (4) of Civil Code and Article 81 number 33 of Law Number 11 of 2020 which confirms that the workers positioned as preferred creditors for unpaid wages and other rights. As well as the existence of discrepancies in Decision Number 274/Pdt.Sus-PKPU/2020/PN Niaga.Jkt.Pst related to expiration of time period in deciding on homologation decisions as stipulated in Article 284 (4) of Law Number 37 of 2004.